Primary hydatid cyst of the neck - EPSC 101593 - Mohammad Tareq Rahimi; Reshadullah Jurat; Mohammad Akbar Shirzad; Haseeb Rahman (Elsevier, 2020)
Hydatid cyst is a parasitic infection mostly caused by Echinococcus granulosis. The most frequent sites of the cyst are liver and lungs. Occurrence in the head and neck region is extremely rare. Only a few cases of hydatid cyst located in head and neck have been reported in the literature. The diagnosis of such isolated neck hydatid cyst is challenging due to the presence of simulating and more common cystic pathological conditions in the neck. Despite the fact that imaging techniques are sensitive in diagnosing cystic lesions, sometimes they cannot accurately identify etiology of the lesion. Here we are reporting a case of isolated primary hydatid cyst of the neck.